2015
DOI: 10.3109/01443615.2015.1011106
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of uterus-preserving treatment modalities for abnormally invasive placenta

Abstract: This is a systematic review for evaluating failure rates (secondary hysterectomy or maternal mortality) and success rates (subsequent menstruation or pregnancy) following radiological or conservative surgical interventions for abnormally invasive placenta (AIP). Twelve cohort studies and 8 case series or case reports were included. The cumulative outcomes showed success rates of 159/177 (89.8) for arterial embolisation, a secondary hysterectomy in 20/177 (11.3%), a subsequent menstruation in 74/85 (87.1%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 39 publications
0
22
0
1
Order By: Relevance
“…34,35 A systematic review including 177 cases of PAS disorders reported success rates of 90% for arterial embolization, with secondary hysterectomy necessary in only 11.3%. 39 In the remaining 85 women, subsequent menstruation occurred in 87% and three women had a subsequent pregnancy. The indications for embolization and the depth of villous invasion are not accurately reported by the authors, limiting the interpretation of the data.…”
Section: Preventive Surgical or Radiological Uterine Devascularizationmentioning
confidence: 98%
See 2 more Smart Citations
“…34,35 A systematic review including 177 cases of PAS disorders reported success rates of 90% for arterial embolization, with secondary hysterectomy necessary in only 11.3%. 39 In the remaining 85 women, subsequent menstruation occurred in 87% and three women had a subsequent pregnancy. The indications for embolization and the depth of villous invasion are not accurately reported by the authors, limiting the interpretation of the data.…”
Section: Preventive Surgical or Radiological Uterine Devascularizationmentioning
confidence: 98%
“…A systematic review including 177 cases of PAS disorders reported success rates of 90% for arterial embolization, with secondary hysterectomy necessary in only 11.3% . In the remaining 85 women, subsequent menstruation occurred in 87% and three women had a subsequent pregnancy.…”
Section: “Leaving the Placenta In Situ” Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…180 A more recent systematic review showed that uterus preserving surgery is associated with a success rate of 48/76 women (63.2%), a secondary hysterectomy in 23/76 women (30.0%), maternal mortality in 2/54 women (3.7%), subsequent menstruation in 20/37 women (81.1%) and subsequent pregnancy in 21/27 women (77.8%). 181…”
Section: Evidence Level 2+mentioning
confidence: 99%
“…Arterial balloon occlusion catheters have been associated with a success rate of 33/42 (78.6%) and the need for a secondary hysterectomy in 8/42 (19%). 181…”
Section: Evidence Level 2àmentioning
confidence: 99%